1997
DOI: 10.1021/bi962245n
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Requirement for Trimethylation of Yeast Cytochromec

Abstract: Lysine 72 (using the vertebrate numbering system) is trimethylated in cytochromes c from fungi and plants but not from higher animals. We have investigated the characteristics of an amino acid sequence required for trimethylation of lysine 72 by examining 21 altered iso-1-cytochromes c from Saccharomyces cerevisiae having single replacements in the region encompassing residues 67 through 77. These results indicated that tyrosine 74 is critical for trimethylation of lysine 72, whereas replacements at other posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
(39 reference statements)
1
11
0
Order By: Relevance
“…The lack of methylation at any site other than Lys-72 is consistent with the results of Takakura et al (32), who investigated the amino acid sequence requirement for trimethylation of Lys-72 by examining 21 altered iso-1-cytochromes c having single replacements in the region encompassing residues 67 through 77. Their study revealed that tyrosine 74 is critical for trimethylation of Lys-72, whereas replacements at other positions did not produce significant diminutions.…”
Section: Ctm1p Is a Methyltransferase That Specifically Acts On Cytocsupporting
confidence: 87%
“…The lack of methylation at any site other than Lys-72 is consistent with the results of Takakura et al (32), who investigated the amino acid sequence requirement for trimethylation of Lys-72 by examining 21 altered iso-1-cytochromes c having single replacements in the region encompassing residues 67 through 77. Their study revealed that tyrosine 74 is critical for trimethylation of Lys-72, whereas replacements at other positions did not produce significant diminutions.…”
Section: Ctm1p Is a Methyltransferase That Specifically Acts On Cytocsupporting
confidence: 87%
“…Despite findings that trimethylation does affect the molecule in subtle ways (22,30), the biological reason for retaining the methylase through evolution in yeast has remained elusive (18,19). Our finding that trimethylation blocks pro-apoptotic activity initially promised a resolution to this issue.…”
Section: Discussionmentioning
confidence: 87%
“…Specific lysine residues are methylated in cytochromes c from certain eukaryotes, including fungi, plants, and some protozoa, but not in animals (18,19). Cytochromes c from many fungi, including Saccharomyces cerevisiae, contain trimethyllysine at the single position 72 (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These considerations suggest that the SET domain methyltransferase Efm1 modifies lysine 390, although this needs to be experimentally confirmed. It is important to note that the overall native structure of at least one substrate protein for SET domain methyltransferases has been observed to be required for substrate recognition and this may be a determining factor rather than, or in addition to, the primary sequence [31]. …”
Section: Resultsmentioning
confidence: 99%